Lights out? The Outlook for Energy in Eastern Europe and Central Asia - World Bank (World Bank, 2012)
Before the current economic crisis hit the Europe and Central Asia (ECA) region in 2008, energy security was a major source of concern in Central and Eastern Europe and in many of the economies in the former Soviet Union. Energy importers were experiencing shortages leading to periodic brownouts and blackouts. An energy crisis seemed imminent. This report analyzes the outlook for energy demand and supply in the region. It estimates the investment requirements and highlights the potential environmental concerns associated with meeting future energy needs, including those related to climate change. The report also proposes the actions necessary to create an attractive environment for investment in cleaner energy. Greater regional cooperation for smart energy and climate action is an important part of the World Bank's engagement in Europe and Central Asia.